2005
DOI: 10.1111/j.1523-1755.2005.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Can murine diabetic nephropathy be separated from superimposed acute renal failure?

Abstract: By careful optimization of STZ dose, a stable and reproducible diabetic murine model was established. However, even in this optimized model, renal functional impairment was observed. The frequency of ATN and functional impairment casts doubt on conclusions about experimental diabetic nephropathy drawn from reports in which ATN has not been excluded rigorously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 18 publications
2
91
1
3
Order By: Relevance
“…STZ is a DNA-alkylating reagent, and single large doses produce tubular necrosis, but repeated lower doses and the resulting hyperglycemia produce glomerular changes more typical of, but not identical to, diabetic nephropathy (29). The observations here do not rigorously rule out the possibility that the improvements in the glomeruli were secondary to the lower blood glucose levels in the treated diabetic mice.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…STZ is a DNA-alkylating reagent, and single large doses produce tubular necrosis, but repeated lower doses and the resulting hyperglycemia produce glomerular changes more typical of, but not identical to, diabetic nephropathy (29). The observations here do not rigorously rule out the possibility that the improvements in the glomeruli were secondary to the lower blood glucose levels in the treated diabetic mice.…”
Section: Discussionmentioning
confidence: 47%
“…The mice do not spontaneously develop diabetes but lack functional B and T cells and have lymphopenia and hypogammaglobulinemia together with a normal hematopoietic microenviron-ment (28). Multiple low doses of STZ were administered to the mice (Scheme 1) under conditions that tend to minimize nephrotoxicity from the drug (29). In initial experiments, we administered 35 mg͞kg STZ daily for 5 days following the protocol of Hess et al (9), but the mice either died or had to be killed after 3-5 weeks because of severe weight loss and cachexia.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we postulate that the HO-2 deletion is responsible for the impairment in renal functional and histologic alterations that were observed and amplified as a result of STZ-induced diabetes in HO-2 (Ϫ/Ϫ) mice. Recently, Tay et al (18) also reported STZ-induced renal toxicity with acute tubular necrosis in the murine model of diabetic nephropathy. Consonant with our findings in the wild type, renal functional impairment without evidence of histologic damage was noted even at very low doses of STZ (75 mg/kg) by these authors.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our data, it is clear that HO-2 deficiency per se contributes to renal dysfunction. It is known that STZ alone may be an instigator of the renal tissue injury manifested by an increase in plasma creatinine and tubular injury and expression of Ig antigen (18,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation